Practices of Claiming Control and Independence in Couple Therapy With Narcissism - Janusz, Bernadetta; Bergmann, Jörg R.; Matusiak, Feliks; Peräkylä, Anssi (Frontiers in Psychology, 2021)
Four couple therapy first consultations, identified by therapists as difficult interactions and involving clients with diagnosed narcissistic problems, were examined. A sociological enriched and broadened concept of narcissistic disorder was worked out based on Goffman's micro-sociology of the self. Conversation analytic methods were used to study in detail moments in which manifest interactional difficulties, such as interruption of the flow of interaction, occurred.Through inductive analysis, the difficulties were traced back to three interactional processes: the clients' efforts to control (1) the sequential position of their utterances, (2) the topical development of the interaction, and (3) the displays of their declarative and performative identities. These efforts to control were interpreted as responses to the threats that the first couple therapy consultation imposes upon the clients' self-image. The results were discussed in the light of contemporary psychiatric discussions on narcissism: they suggest that the internal experience in persons with narcissism is inextricably intertwined with interactional practices.